Covalent fragment inhibits intramembrane proteolysis - Eden, Angela; Zhao, Jing; Xiao, Yuanyuan; Gibson, James; Wang, Chunyu (Frontiers in Molecular Biosciences, 2022)
Alzheimer’s disease (AD) is a serious public health crisis with only one current modifying treatment. The reduction of amyloid load by targeting γ-secretase (GS) has been a leading approach in AD drug discovery and development. Despite the focus on GS inhibition multiple GS inhibitors (GSIs) have failed in clinical trial as a result of side effects such as worsening cognitive decline. These side effects are largely attributable to inhibition of normal functions of GS such as cellular signaling. Standard enzyme inhibitors target catalytic or allosteric sites of the enzyme as previous GSIs did. To avoid issues observed from broad spectrum GSIs we discovered fragment 6H8 that covalently binds to the substrate of GS, the transmembrane domain of amyloid precursor protein (APPTM). NMR combined with MALDI-TOF-MS established 6H8 covalently binds to APPTM. 6H8 acting as a Michael acceptor covalently links to the sidechain amines of lysine residues specifically targeting a cluster of C-terminal lysines K53 – K55. 6H8 can inhibit intramembrane proteolysis of an archaeal homolog of the presenilin (the active subunit of GS) via substrate binding in a gel-based cleavage assay with a 2 – 4 μM IC50. 6H8, while too small to be considered a drug candidate on its own, it is poised to be used as an effective covalent warhead of a targeted covalent inhibitor (TCI) that combines a specific non-covalent binder to a potent covalent warhead. The further development of the 6H8 fragment into the covalent warhead of a TCI is to our knowledge a novel approach in AD drug discovery.